NAKED ANXIETY: BATHHOUSES, NUDITY, AND THE DHIMMĪ WOMAN IN 18TH-CENTURY ALEPPO - Semerdjian, Elyse (International journal of Middle East studies, 2013)
In the 18th century, non-Muslims and women crossed social boundaries during a period of increased global consumption, prompting intervention on the part of Ottoman officials. On the imperial level, the sultan promulgated edicts to restrict such crossings, following the path of earlier laws that had regulated public spaces including bathhouses. In Aleppo, a local reflection of these 18th-century trends was increased monitoring of nudity and of contact between Muslims and non-Muslims within the city's bathhouses. Regulations required that bathkeepers provide separate bath sundries for Muslims and non-Muslims and prohibited co-confessional bathing for women in particular. With the assistance of guilds—and to a lesser extent millet representatives—complex bathing schedules for Muslim and non-Muslim women were registered at court to support segregation policies. Jurists discussing modesty requirements for Muslim women declared that non-Muslim (dhimmī) women were to be treated as unrelated men in that they were forbidden to gaze upon a naked Muslim woman. Shariʿa court rulings were constructed along similar lines, indicating that the dhimmī woman was an unstable, liminal social category because in some circumstances her gaze was gendered male. Muslim male elites and local guilds ultimately instituted segregated bathing schedules to protect the purity of Muslim women from the danger posed by the dhimmī female figure.